Assessing climate change impacts on plant production and irrigation water demand at country level: analysis for Iran - Soltani, Afshin; Pourshirazi, Shabnam; Torabi, Benjamin; Rahban, Samaneh; Alimagham, Seyyedmajid (Journal of Agriculture and Environment for International Development (JAEID), 2025)
Climate change poses a critical challenge to plant production and food security. A comprehensive report on the effects of climate change on the production of all major agricultural crops in the entire country level is currently lacking. We assessed the impact of climate change on 35 key agricultural plant species by analyzing crop yield under irrigated and rainfed conditions, and examining net irrigation water volume (IWV) at the country level for Iran as example case. The entire country was covered using the SSM-iCrop2 crop model. Rainfed or irrigated conditions, climate type, and crop species influenced the results. Results revealed that, except for wheat and rapeseed under rainfed conditions, climate change had either neutral or negative effects on crop yields. Rainfed cool-season pulses and barley showed no benefits from climate change, while under irrigated conditions, crop yields were projected to decline more significantly for plant species and climate zones currently experiencing higher temperatures. Warm-season crops experienced yield reductions of 8-12%, whereas cool-season crops saw smaller declines of around 5%. At the national level, the net impact of climate change on plant production was a 9% decrease under irrigated conditions and a 16% increase under rainfed conditions, largely due to the dominance of wheat and rapeseed as major rainfed crops. However, the 9% decline in irrigated systems is particularly concerning, as 92% of Iran’s plant production relies on irrigation. Additionally, while IWV decreased by 7.5% nationwide—primarily due to reduced water use for wheat, barley, and rapeseed—the challenge of adapting Iran’s agriculture to water scarcity remains greater than that posed by climate change alone. These findings highlight the need for future research focused on optimizing water and land resource allocation to sustain plant production in a changing climate.